ANALISIS JUMLAH MAHASISWA/I BARU DENGAN MENGGUNAKAN REGRESI LINIER SEDERHANA - Ningsih, Murni; Hafel, Rahmadhani; Septa, Giar (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2024)
Student development in recent years has shown a state of improfement. Howefer, event though there has been an incrause, future predictions need to be made to find out the number of students in the following year. This aim is to find out how lacturers and student compare in terms of numbers, provide space for the lecture process and other supporting facilities. In this research, the sampels taken were students from the faculty of economics and digital business from 2019 to 2024. Academic year is the independent variable, and the estimated number of new students is the dependent variable. Furthermore, student data from the faculty of economics and digital business was used. These students are divided into two study programs, namely entrepreneurship and digital business. The results of this research show that the prediction for entrepreneurship study program students is 4.52, and the digital business study is 7.76, which allows us to identify new students in the future.